Reduction in the resistance of poly(3, 4-ethylenedioxythiophene):poly(styrene sulphonate) (PEDOT:PSS) films by sequential chemical treatment. (15th December 2022) - Sharma, Meenu; Sameera, I.; Bhatia, Ravi
Abstract: The effect of sequential chemical treatment on the room temperature electrical resistance of sub-micron-thick poly(3, 4-ethylenedioxythiophene):poly(styrene sulphonate) (PEDOT:PSS) films was studied. The resistance of PEDOT:PSS films was found to be highly dependent on the molar concentration, type of solvent and number of successive treatments. An effective decrease in the resistance value from ∼415 Ω to ∼35 Ω was achieved upon successive treatments of pristine film twice with dimethyl sulfoxide and one time with 0.5 M sulfuric acid. Interestingly, the resistance of the film was found to depend on the sequence of the successive treatment of both the solvents. The appearance of sharp peak in XRD after acid treatment suggests enhancement in the crystallinity of the PEDOT:PSS films. Raman spectroscopy was employed to monitor the structural changes (coil to extended linear coil conformation) that results in an improvement in the conductance of the treated films. Highlights: Tuning the resistance of PEDOT:PSS films by solvent treatment. Influence of molarity and number of successive treatments on the resistance was studied. Effect of sequence of successive treatments on the resistance was elucidated. Role of sequential treatment on the structural properties was probed by AFM, XRD and Raman spectroscopy.